Caracterización geológica-geotécnica en la vía La Saquea – Cantzama bajo desde el tramo absc 0+000 hasta 5+850, ubicada en las parroquias Cumbaratza y Guadalupe, cantón Zamora, provincia de Zamora Chinchipe. - Bravo Fajardo, Lilibeth Johana (2022)
The present investigation entitled "Geological-geotechnical characterization in La Saquea - Cantzama Bajo road from the absc section 0+000 to 5+850, located in the Cumbaratza and Guadalupe municipalities, Zamora canton, Zamora Chinchipe province" focuses on the geological - geotechnical description of the section of road under study in order to identify geological and structural characteristics present in the area, determine the physical - mechanical properties of existing geomaterials. The study area corresponds to an extension of 5.85 km and covers a total area of 65.61 ha. Firstly, geological description of the study site was carried out based on the topography provided by Provincial GAD of Zamora Chinchipe and critical analysis zones were identified. Characterization was carried out for the rock masses conformed of basaltic andesite and micaceous schist, as well as for the two landslides conformed of clayey silt with sand and sabulo. Consecutively, samples were collected for the respective laboratory tests, being direct shear for soil and simple compression for rock. Likewise, four pits were made near the study slopes to observe the presence of water table and obtain soil samples to carry out classification tests. In addition, two seismic lines were developed in order to corroborate the geology and obtain physical properties of the materials. In the case of rock masses, their geomechanical classification was made using RQD, RMR, GSI and SMR to determine the stability of the previously mentioned slopes. The resistance analysis of the rock mass was developed using the generalized Hoek & Brown criterion adjusted to the Mohr - Coulomb criterion. Finally, the global stability of the slopes in the current state and with seismic load was analyzed: obtaining safety factors from Critical State for the case of soil slopes and rock mass No. 1 to Stable for the two remaining rock masses. Keywords: geomechanical classification, Hoek-Brown and Mohr-Coulomb standards, safety factor, geomaterials, rock masses.